Particular Semantic and Syntactic Properties of Polyfunctional Lexeme LI - V. N. Zavialov; Xu Ma (Научный диалог)
The object of the article is a non-descriptive lexeme. Its use is investigated in various semantic-syntactic and communicativepragmatic contexts. The relevance of the work is due to the need for amore holistic description of a number of primitive linguistic units (a, and, either, or, etc.), the categorical properties of which are not fully and systematically identified within the framework of traditional methods of analysis. The novelty of the work lies in the consideration of all uses within the framework of the functioning of the lexeme-particular of the same name. This approach is due to the principles of nonparadigmatic linguistics — a modern trend in the study of primitive lexemes. The theoretical significance of the work lies in the introduction into scientific circulation of the principles of the analysis of a particular li based on its ancient categorical properties associated with the semantics of conjecture. It has been established that in all the considered contexts we are dealing with the same particular lexeme, which retains its original categorical properties in them. They are manifested in the questioningness of li (direct or indirect), as well as in various hypothetical meanings that are realized in sentences-statements at a deep syntactic level. Asimilar description technique is applicable to the analysis of the properties of other particular units of the Russian language.